Engenharia forense: estudo de microvestígios coletados em locais de crime (touch DNA) - Barbosa, Carlos de Almeida (2017)
The last decades have brought great technological advances to the Forensic Sciences. The Molecular Biology has been used as a tool for human identification since the 80´s, and it has bought fantastic results from this application, being a landmark in the evolution of Forensic Science. Since this decade, new studies have been carried out in this area. Traces found in crime scenes are elements that can guide the search for the elucidation of the facts. There are two types of traces: macro-traces, that are easily identified and micro-traces that requires more specific technical analysis. One of the traces is the digital fingerprint, that is a possible source of DNA extraction, with great potential for recovery of the genetic material. This research has the purpose to analyze samples collected from fingerprints on various objects chosen as deposition surface, such as glass, metal, plastic, wood and masonry wall. This research shows that it is possible to establish a connection between DNA samples and fingerprints. Samples have been collected from intact and intact smears and fingerprints intact and smeared with powder. The results showed the feasibility of using this type of sample, based on the DNA recovery and the success of the genotyping. The results obtained in the different matrices analyzed showed greater results in the metal surface, where it was possible to obtain a complete genetic profile in all the samples Collected and analyzed. In the glass matrix, either the samples "latent intact" or in "latent smear" it was possible to recover genetic profile with more than 17 amplified loci. In the "intact and powder smear" samples, even with confirmation of the presence of DNA, the quantities recovered were insufficient to generate the electropherogram. In the wood matrix, such as in the plastic matrix, the presence of DNA was observed, but at low concentration to generate the electropherogram. Finally, the samples collected from the "latent intact" and "intact with powder" masonry wall samples, respectively, showed amplification of 17 and 19 loci of the 24 present in the kit. Some Studies and experiments have been done in the Forensic Molecular Genetics Laboratory of Scientific Police in Paraná with positive results in many cases, identifying suspects and contributing to the Integrated Network of Gene Prolifiling Banks (RIBPG). These studies have made this methodology feasible. The results show the efficiency and the possibility of obtaining a genetic profile from this type of sample, making this one more important pericial tool.